The Role of Islamic Religious Education Teachers in Integrating Moral Values into Digital Media-Based Ablution Learning at SDIT Permata Bunda - Ahmad Mujib; Meti Fatimah (Abjadia : International Journal of Education, 2026)
This study aims to examine the role of Islamic Religious Education (IRE) teachers in integrating moral values and utilising digital media in ablution learning at SDIT Permata Bunda. This study employed a descriptive qualitative approach involving Islamic Religious Education teachers and upper-grade students as research participants. Data were collected through observation, interviews, and documentation, and analysed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings indicate that IRE teachers play a highly strategic role in shaping students’ moral character through ablution learning, implemented through role modelling, habituation, reflective dialogue, and positive reinforcement. The use of digital media, such as animated videos, 3D simulations, and infographics, was found to enhance students’ technical understanding of ablution while strengthening the internalisation of moral values by presenting moral messages in an engaging and contextual manner. Digital media also encourages active student participation and aligns with the characteristics of the digital generation. Despite challenges related to limited digital devices and teachers’ digital literacy, adaptive strategies implemented by teachers ensured that the objectives of moral education were achieved. This study is limited to a single educational institution within a specific geographical context, and therefore the findings cannot be generalised broadly. Overall, ablution learning that integrates teacher role modelling and digital media utilisation plays a significant role in fostering students’ Islamic character holistically.